Targeted Biological Effect of An Affitoxin Composed of an HPV16E7 Affibody Fused with Granzyme B (ZHPV16E7-GrB) Against Cervical Cancer In vitro and In vivo - Wang, Wenhuan; Tan, Xiaochun; Jiang, Jie; Cai, Yiqi; Feng, Fangfang; Zhang, Lifang; Li, Wenshu (Current Cancer Drug Targets, 2021)
Background: High risk type 16 of human papillomavirus (HPV16) is associated with 50% of cervical cancer, for which reliable targeted therapies are lacking. HPV early protein 7 (E7) is an oncoprotein responsible for cell malignant transformation. In our previous work, a highly specific affibody targeting HPV16E7 (ZHPV16E7) was developed. Objective: In order to improve the targeted therapeutic effect, the present study prepared an affitoxin consisting of ZHPV16E7 fused with granzyme B (GrB), namely, ZHPV16E7-GrB, and evaluated its targeting action in vitro and in vivo. Methods: The ZHPV16E7-GrB fusion protein was produced in a prokaryotic expression system. The targeted binding properties of the ZHPV16E7-GrB to the HPV16E7 were confirmed by immunofluorescence assay (IFA) in cervical cancer cell lines, by immunohistochemical assay (IHA) in cervical cancer tissue from clinical specimens and by near-infrared imaging in tumour-bearing mice. The anti- tumour effect on both cervical cancer cells in vitro and tumour-bearing mice in vivo were further evaluated. Results: A 34-kDa ZHPV16E7-GrB fusion protein was produced in E. coli and displayed the corresponding immunoreactivity. IFA revealed that ZHPV16E7-GrB bound specifically to HPV16-positive TC-1 and SiHa cells. IHA showed that ZHPV16E7-GrB also bound specifically to HPV16-positive clinical tissue specimens. In addition, the near-infrared imaging results showed that ZHPV16E7-GrB was enriched in tumour tissues. Moreover, both the ZHPV16E7-GrB affitoxin and ZHPV16E7 affibody (without GrB) significantly reduced the proliferation of cervical cancer cells in vitro and tumor-bearing mice in vivo, and the anti-proliferative effect of ZHPV16E7-GrB was higher than that of the ZHPV16E7 affibody. Conclusions: The affitoxin by coupling the affibody with GrB is a promising targeted therapeutic agent with the dual advantages of the targeted affibody and the GrB cytotoxin.
Keywords: targeted effect